Plasmin Induces Local Thrombolysis without Causing Hemorrhage: A Comparison with Tissue Plasminogen Activator in the Rabbit - Marder, Victor J.; Landskroner, Kyle; Novokhatny, Valery; Zimmerman, Thomas P.; Kong, Mansze; Kanouse, Joel J.; Jesmok, Gary (Thrombosis and Haemostasis, 2001)
The direct fibrinolytic enzyme, plasmin, was compared with tissue plasminogen activator (TPA) in rabbit models of local thrombolysis and fibrinolytic hemorrhage. Plasmin was produced by solid-phase urokinase activation of plasminogen and purified on benzamidine Sepharose. Applied as an intra-arterial infusion into the thrombosed abdominal aorta under conditions of unimpeded blood flow, plasmin (4 mg/kg) and TPA (2 mg/kg) achieved equivalent clot dissolution and flow restoration. Using the model of restricted blood flow into the thrombosed aorta, which limits local plasminogen supply, plasmin was superior to TPA in clot lysis and vascular reperfusion. Using similar dosages of plasmin (2 or 4 mg/kg) and TPA (1 or 2 mg/kg) in the earpuncture rebleed model. TPA induced rebleeding in a dose-dependent manner from prior puncture sites in 9 of 10 animals, while none of the 10 animals exposed to plasmin rebled from these sites.These results suggest that plasmin is an effective, unique thrombolytic agent, distinguished from the plasminogen activators in current usage by its striking safety profile.
Keywords: Plasmin; TPA; thrombolysis; hemorrhage; rabbits